2012
DOI: 10.5704/moj.1211.007
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Calcaneoplasty in Insertional Achilles Tendinopathy

et al.

Abstract: Calcaneoplasty, Insertional Achilles tendinopathy, Haglund's deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Specifically, the rate of complications with open surgical debridement for Achilles tendinopathy ranges from 6 to over 30%. [44][45][46][47][48][49] The complication rate for plantar fasciotomy surgery has been reported to range from 4.0 to 4.4%. 50,51 Similarly, a review of endoscopic plantar fascia release reported a complication rate of 6.0%, including paresthesias or numbness, soft tissue healing, and superficial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the rate of complications with open surgical debridement for Achilles tendinopathy ranges from 6 to over 30%. [44][45][46][47][48][49] The complication rate for plantar fasciotomy surgery has been reported to range from 4.0 to 4.4%. 50,51 Similarly, a review of endoscopic plantar fascia release reported a complication rate of 6.0%, including paresthesias or numbness, soft tissue healing, and superficial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the lower extremities, USG surgical procedures may have a notably lower complication rate than traditional surgical techniques. Specifically, the rate of complications with open surgical debridement for Achilles tendinopathy ranges from 6 to over 30% 44–49 . The complication rate for plantar fasciotomy surgery has been reported to range from 4.0 to 4.4% 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, when there is major intratendinous bone pathology involved, in clinical practice surgery is often warranted. Surgical techniques [5][6][7][8][9][10][11][12][13][14][15][16][17][18] include procedures such as tendon detachment-bone removal-tendon re-attachment and calcaneo-osteotomy. Bone removal via longitudinal tenotomy is an alternative when there is minor bone pathology.…”
Section: Introductionmentioning
confidence: 99%